2015
DOI: 10.1890/es14-00360.1
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation of resistance to water loss within two species of lungless salamanders: implications for activity

Abstract: Citation: Riddell, E. A., and M. W. Sears. 2015. Geographic variation of resistance to water loss within two species of lungless salamanders: implications for activity. Ecosphere 6(5):86. http://dx.doi.org/10.1890/ES14-00360.1Abstract. For many organisms, constraints on activity increase energetic costs, which ultimately reduce the suitability of a particular habitat. Mechanistic species distribution models often use estimates of activity to predict how organisms will respond to climate change. These models co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 56 publications
1
61
1
Order By: Relevance
“…This is contrary to our prediction, as smaller salamanders are expected to have higher rates of water loss per unit area [23]. While studies have found evidence for geographic variation in desiccation resistance indicative of local adaptation based on gradients of environmental moisture e.g., [82,83] it is notable that we did not find evidence for plasticity in resistance to water loss based on our moisture treatments. This result has important implications for the ability of salamanders to respond to changes in environmental moisture.…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to our prediction, as smaller salamanders are expected to have higher rates of water loss per unit area [23]. While studies have found evidence for geographic variation in desiccation resistance indicative of local adaptation based on gradients of environmental moisture e.g., [82,83] it is notable that we did not find evidence for plasticity in resistance to water loss based on our moisture treatments. This result has important implications for the ability of salamanders to respond to changes in environmental moisture.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study on water loss rates in lungless salamanders found mixed results, with one species adapted to cope better with dehydration at lower altitudes and a second species better suited for higher altitudes (Riddell & Sears, ). The apparent contradiction between microclimatic and physiological measurements might be explained if we consider variation instead of the average values of microclimatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…reduction in rates of water loss) during acclimation to warm temperatures. We based our prediction upon previous experiments in which salamanders used warm temperatures as a cue to adjust water loss rates (Riddell & Sears ). However, if normalV˙normalO2 did not decline, we predicted that individuals might increase heart rates to promote oxygen delivery (Franklin et al., ).…”
Section: Introductionmentioning
confidence: 99%